EVALUATION OF HYPOGLYCEMIC ACTIVITY OF THE POLYSACCHARIDES EXTRACTED FROM LYCIUM BARBARUM - Jing, Longjun; Cui, Guowen; Feng, Qiang; Xiao, Yuanshi (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
A study was undertaken to evaluate the hypoglycemic activity of polysaccharide extracted from Lycium barbarum (LBP). The various parameters studied included body weight (bw), fasting blood glucose levels (FBG), total cholesterol (TC) and triglyceride (TG) in diabetic and normal mice. LBP treatment (20, 40 mg/ kg body weight) for 28 days resulted in a significant decrease in the concentration of FBG, TC and TG in diabetes mellitus mice. Furthermore, LBP significantly increased body weight. The data demonstrated LBP at the dose of 40 mg/kg bw exhibited the better effect.